EFEKTIVITAS MEDIASI DALAM PERKARA WANPRESTASI DI PENGADILAN NEGERI BANGKINANG - Haris Nasution; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
One of the peace efforts that can be carried out by third parties in helping to resolve civilmatters, especially default both inside and outside the court, is mediasai, mediation is basicallynegotiations involving third parties who have expertise on effective mediation procedures, canhelp in conflict situations to coordinate their activities so that they are more effective in theprocess of bargaining, as stipulated in the Supreme Court Regulation Number 1 of 2016concerning Procedures for Mediation in Courts, in the settlement of civil disputes throughmediation there are several stages based on mediation procedures in the court, namely the premediationstage, the mediation stage, the final stage of the mediation result implementation.In fact, in the Kampar District Court the mediation remained the most way out inresolving default cases in the Kampar District Court, but in reality mediation had not been ableto reduce the failure rate in resolving the default cases, the factors of the parties, the factor ofthe mediator judge, the number of mediators, the cost factor for the mediator profession.This study aims to determine the effectiveness of the mediation applied in the KamparDistrict Court in a default case in the Kampar District Court. The type of research used isempirical juridical research, with sample selection. The data studied included primary dataand secondary data, then analyzed qualitatively. This research was conducted in the KamparDistrict Court. Population and sample are all parties related to the problems examined in thisstudy, the data sources used are primary data, secondary data, and tertiary data. Datacollection techniques in this study are interviews, questionnaires and literature studies. Fromthe results of the study showed that mediation effectiveness shows the number of failures withvarious factors or constraints such as case factors, parties' factors and mediator factors. Themediation has also not been able to reduce the number of failures in resolving default casesand overcoming cases that have accumulated in the Court.Keywords: Effectiveness - Mediation - Default - District Court